2008
DOI: 10.1111/j.1939-165x.2008.00055.x
|View full text |Cite
|
Sign up to set email alerts
|

Cross‐reactivity of anti‐chicken IgY antibody with immunoglobulins of exotic avian species

Abstract: The results demonstrate that some commercially available anti-chicken IgY antibodies exhibit good cross-reactivity with most avian species.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 14 publications
1
12
0
Order By: Relevance
“…In this study, the use of anti-macaw IgY secondary antibody in the dot-blot ELISA for testing antibody-positive Blue and gold macaw plasma generated appreciably better visible signals with consistently higher signal intensity than the use of antibird, anti-duck, or anti-chicken IgY secondary antibodies ( Figure 2; Table 1). Though some studies have used antichicken secondary antibody in serologic assays in wild birds, 28,29 our results were in agreement with a study that found the use of anti-passerine IgY secondary antibody in a microplate ELISA performed better than anti-chicken and anti-bird secondary antibodies when testing passerines. 25 In fact, we found that the use of antimacaw IgY secondary antibody, in both the Western blot and the dot-blot ELISAs, showed strong species specificity for psittacines.…”
Section: Discussionsupporting
confidence: 91%
“…In this study, the use of anti-macaw IgY secondary antibody in the dot-blot ELISA for testing antibody-positive Blue and gold macaw plasma generated appreciably better visible signals with consistently higher signal intensity than the use of antibird, anti-duck, or anti-chicken IgY secondary antibodies ( Figure 2; Table 1). Though some studies have used antichicken secondary antibody in serologic assays in wild birds, 28,29 our results were in agreement with a study that found the use of anti-passerine IgY secondary antibody in a microplate ELISA performed better than anti-chicken and anti-bird secondary antibodies when testing passerines. 25 In fact, we found that the use of antimacaw IgY secondary antibody, in both the Western blot and the dot-blot ELISAs, showed strong species specificity for psittacines.…”
Section: Discussionsupporting
confidence: 91%
“…The serum samples were added at 1:500 dilution and after 30 minutes of the incubation and three washings, were incubated with the anti-chicken IgY peroxidase conjugate (Sigma Chemicals) for 1 h at 37 °C. These anti-chicken IgY antibodies had cross-reactivity with IgY of penguin as demonstrated by ELISA (date not show) and Western blotting (Cray et al 2008). The relative level of antibody was determined by calculating the sample to positive ratio (S/P).…”
Section: Elisa To Ibdvmentioning
confidence: 99%
“…Coefficients of variation were calculated in Microsoft Excel for each individual colony (North Dakota and South Dakota) and as a group so we could compare variation of food consumed. To accurately determine the concentrations of antibodies within the samples, we devised a modified direct (serum) and indirect (regurgitate) ELISA test (Crowther 2001;Martinez et al 2003;Cray and Villar 2008). It was necessary to devise a novel ELISA test due to the uncertainty of tested IgA and IgY ELISA commercial kits regarding non-chicken avian species (Crowther 2001;Martinez et al 2003;Cray and Villar 2008).…”
Section: Discussionmentioning
confidence: 99%